Socioeconomic status and stressors affecting wellbeing of high school adolescents in Kuala Lumpur: Psychological and behavioural outcomes / Sharifah Muhairah Shahabudin - Shahabudin, Sharifah Muhairah (2014)

(untitled)
Past studies have found that socioeconomic status (SES) impacts social and psychological development of children and adults. Although these relationships are documented, there is ongoing debate on the operationalization of SES and the adequacy of conventional indicators of SES (occupation, education, income) in measuring the SES construct in association with wellbeing. To address this gap, this study conceptualizes individuals SES as a function of “capital”, also known as the CAPSES. The CAPSES scale is based on individual’s access to resources such as material capital, human capital and social capital. The objectives of the study is threefold; first, to demonstrate the validity of the CAPSES indicator in relation to adolescents’ psychological and behavioral wellbeing. Second, to ascertain the relationship among CAPSES, stressors, behaviour and depression. Third, to examine the mediating effect of parent, teacher and peer stressors in the relationship between SES and psychological and behavioral outcomes in adolescents. The data was obtained through survey method in secondary schools in Kuala Lumpur, supported with focus group discussions. The study finds that CAPSES serves as a useful indicator of SES and its influence is substantial on parent stressors. The stressors variables appear to be more strongly related to adolescent psychological and behavioral outcomes than SES. Parent stressors had a significant influence over negative mood, peer and teacher stressors, while teacher stressors significantly influenced maladaptive behavior and risky behavior. It was also found that parent and peer stressors played an important role as mediators in the relationship between SES and psychological outcomes. iv To further investigate the influence of CAPSES on the outcomes, the respondents were segregated according to their academic achievements (achievers and under achievers). The findings suggest respondents in the lower SES group who perform well academically are more exposed to feeling stressful with their parents and feeling negative self-esteem whereas higher SES respondents who do not perform well academically face higher possibility of feeling stressful with parents, teachers and peers. The current findings propose that interventions in school are imperative, particularly programs fostering positive peer support.